Molybdenum-oxo Species Deposited on Alumina by Adsorption: III. Advances in the Mechanism of Mo(VI) Deposition - Spanos, N.; Lycourghiotis, A. (Journal of catalysis, 1994)
The refinement of the mechanism of Mo(VI) deposition (proposed previously) from aqueous solutions on the γ-alumina surface by investigating critical mechanistic points is the subject of the present work. A mechanistic model involving the adsorption of Mo7O6−24 and MoO2−4 ions on sites created by the protonated surface hydroxyls of γ-alumina in the inner Helmholtz plane (IHP) of the double layer developed between the surface of the γ-alumina particles and the molybdate solutions, as well as the deposition of the MoO2−4 ions through surface reaction with the neutral surface hydroxyls has been developed; ft has been tested over a wide range of impregnation parameters (pH = 8.5-4.1 at 25°C, temperature 25-50°C at pH = 5 and doping of the carrier with various amounts of Na+ and Li+ ions). The testing of the model included the derivation of various equations corresponding to the model deposition equilibria, the calculation of the amount of the deposited Mo, of the difference in the isotherms of the hydrogen adsorption in presence and absence of molybdates, and of the ζ-potential of the γ-alumina particles in the molybdate solution (using an interactive code for the calculation of chemical equilibria in aqueous systems called SURFEQL), and the comparison of these parameters with the corresponding ones determined experimentally. The agreement between the calculated and experimentally determined parameters over a wide range of impregnating conditions allowed us to shed more light on the mechanism of the Mo deposition. It was established that both the adsorption of Mo7O6−24 and MoO2−4 ions and the deposition of MoO2−4 ions by surface reaction with two neutral hydroxyls of the support take place, but the contribution of each of these processes depends on the impregnating conditions. Specifically, in the pH range 8.5-6. 1 the deposition practically occurs through the reaction of MoO2−4 ions with neutral surface hydroxyls of the support resulting in the formation of the surface complex [formula] whereas at pH = 5 the adsorption of Mo7O6−24 and MoO2−4 ions is predominant and at PH = 4.1 the adsorption of Mo7O6−24 ions prevails. Increasing the impregnating temperature, at pH = 5, from 25 to 50°C increases considerably the adsorption of Mo7O6−24 ions and decreases further the deposition of MoO2−4 ions by surface reaction, whereas it does not change considerably the extent of adsorption of MoO2−4 ions. Finally, the doping with Li+ and Na+ ions increases both the extent of adsorption of Mo7O6−24 ions and the extent of MoO2−4 deposition by surface reaction, whereas it does not change considerably the extent of adsorption of MoO2−4 ions. Moreover, it was demonstrated that each protonated surface hydroxyl creates one adsorption site and that strong lateral interactions are exerted between the deposited species, mainly between the adsorbed MoO2−4 and Mo7O6−24 ions, through water molecules located at the IHP. On the other hand, comparison of the adsorption constant with the reaction constant demonstrated that the ionic sorptive band is much stronger than the covalent Al-O-Mo bonds on the above-mentioned surface complex. Finally, the fact that the ratio [MoO2−4]b/[Mo7O6−24]b calculated in the bulk solution was always lower than the ratio [MoO2−4]adsorb+react/[Mo7O6−24]adsorb calculated in the deposited state corroborated the finding reported previously that, concerning deposition, the selectivity of the support surface for the MoO2−4 ions is higher than the selectivity for the Mo7O6−24 ions.